Preserving Vision in the COVID-19 Pandemic: Focus on Health Equity - Mike EV (Dove Medical Press, 2020)
Elise V Mike,1 Daniel Laroche2,3 1Medical Scientist Training Program, Albert Einstein College of Medicine, Bronx, NY, USA; 2Department of Ophthalmology, New York Eye and Ear Infirmary, Icahn School of Medicine of Mount Sinai, New York, NY, USA; 3Department of Ophthalmology, Advanced Eyecare of New York, New York, NY, USACorrespondence: Daniel LarocheAdvanced Eye Care of New York, 49 West 127th Street, New York, NY 10027, USATel +1 212 663 0473Fax +1 917 493-1010Email dlarochemd@aol.comAbstract: The coronavirus 19 (COVID-19) pandemic has overwhelmed our healthcare systems and caused the deaths of tens of thousands of Americans. Black and Hispanic individuals comprise a disproportionate number of those deaths, primarily because of pre-existing health conditions such as hypertension, obesity, and asthma. Health inequities that underlie these disparities also exist within ophthalmology around the world, and more ophthalmologists should advocate for healthcare reform that advances health equity. Immediate actions to reduce health disparities in ophthalmology during the pandemic include taking time to ensure all ophthalmology leadership and industry is diversified with people reflecting the fabric of their countries, embracing telemedicine to increase access to medical care, and advocating for legislation that will increase health insurance coverage during this unprecedented time. Longitudinal actions include recognizing structural racism as a root cause of health inequity and actively rejecting it through addressing modifiable risk factors, increasing cultural competency training, promoting diversity in the workforce, and global leadership.Keywords: COVID-19, coronavirus, health equity, health disparities